Enhancing Employee’s Trust and Commitment through Strategic Human Resource Management: A Literature Review - Al Adresi, Alaeldeen Saleh; Mohd Ridzuan, Darun (Human Resource Management Academic Research Society (HRMARS), 2016)
This paper intends to explore the relationship between Strategic Human Resource Management(SHRM) practices, employee trust and organisational commitment. The preliminary framework provides an understanding of the specific role of trust between HRM practices and organisational commitment. A range of relevant literature is explored and a preliminary framework is proposed and discussed. A review of ext a nt literature suggest s various factors affect employee’s behavio u r, trust , and commitment . This framework is set to help managers and decision makers understand the requirements of employees for increasing their trust and commitment and suitable SHRM approaches to that effect . The paper can help HR managers to understand the importance of HR strategies and policies through the integration of organisational support, lead to superior trust and commitment. The propose d preliminary framework is both original and unique that will hop efully contribute towards the enrichment of the relevant literature